GPS-based travel time and delay survey methodology and traffic data analysis - Macababbad, Reigna Jewel Ritz M.
Travel time and delay studies are used to evaluate traffic conditions, determine levels of service and to plan for improvements. Trasportation planners and engineers of the Metro Manila Development Authority (MMDA) still employ the manual or stop watch method using a test car in obtaining travel time and delay data. This method is labor intensive and is prone to human errors as well as biases inherent in the conduct of the field surveys. Thus, it is necessary to develop and demonstrate a more efficient method of visualising traffic characteristics using tools for assessment of road traffic conditions. This method should be an accurate and cost-effective data gathering technique that will facilitate data analysis through spatial presentations.